A systematic review of subcutaneous versus intramuscular or intravenous routes of opioid administration on pain outcomes in cancer and post-surgical clinical populations – challenging current assumptions in palliative care practice. Issue 2 (April 2023) - Fairbairn, Lorna; Schuberth, Anna; Deacon, Laura; Gilkes, Hazel; Montgomery, Victoria; Bennett, Michael I; Mulvey, Matthew R
Objective: The objective of this review is to investigate the use of the subcutaneous route of administration of analgesics, common practice within palliative medicine. Design: Systematic review using consensus approach, direct comparison of subcutaneous route with intravenous and intramuscular routes. Results: The limited available evidence demonstrates non-inferiority of the subcutaneous route in both cancer patients and those post-surgery. Pain management is comparable to other routes. Route-related side effects are rare and systemic side effects are comparable. Conclusion: Pain management is a critical role of palliative medicine. The subcutaneous route of administration offers a viable option for the delivery of parenteral analgesia within all settings, including the community. This review supports current practice, demonstrating equivalence with more invasive routes of administration.